Nonlinear Moment-Based Optimal Control of Wave Energy Converters With Non-Ideal Power Take-Off Systems - Nicolas Ezequiel Faedo; Giuseppe Giorgi; John V. Ringwood; Giuliana Mattiazzo (Volume 8: Ocean Renewable Energy, 2022)
The mechanical-to-electrical energy conversion stage in wave energy devices is commonly affected by losses associated with the power take-off (PTO) system, inevitably leading to non-ideal conversion in practical scenarios. Such behaviour needs to be incorporated within the wave energy converter (WEC) energy-maximising control design procedure, so as to guarantee optimal operation of the device under these non-ideal conditions. Motivated by this requirement, we present, in this paper, a nonlinear moment-based energy-maximising control solution for WECs under non-ideal PTO behaviour. We show that the mathematical formalism proposed always admits a globally optimal energy-maximising solution, facilitating the application of state-of-the-art numerical routines, leading to real-time performance. Numerical results are presented for a heaving point absorber WEC system, illustrating the capabilities of the proposed controller in a non-ideal PTO conversion scenario, including a comparison with a benchmark control str